The Influence of Perceptions Transformational Leadership on Lecturer Creativity with Creative Self Efficacy as Mediator - Azliyanti, Elfitra; Akmal, Akmal; Trianita, Mery (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
The purpose of this study is to identify and examine the role of transformational leadership perceptions and creative self-efficacy in employee (lecturer) creativity. Explanatory study with hypothesis testing is the research methodology employed. Bung Hatta University Lecturers are the study's subject and population. Purposive sampling was used, and the sample criteria were Bung Hatta University Lecturers who have worked for at than one year (n = 170). SEM-PLS (Smart PLS) is the data analysis technique used in this investigation. The research findings from the study of perceptions of transformational leadership have no effect on employee creativity, creative self-efficacy has a positive effect on employee creativity, and creative self-efficacy mediates the relationship of perception and employee creativity.